Evil dead rise [videorecording (DVD)] - Raimi, Sam (Warner Bros. Entertainment, 2023)
Two estranged sisters plan to reunite and work out their issues, but the flesh-possessing demons, deadites, thrust them into a primal battle for survival in the most nightmarish version of family imaginable.